Association of Escherichia coli containing polyketide synthase in the gut microbiota with colorectal neoplasia in Japan. Issue 1 (22nd November 2021) - Iwasaki, Motoki; Kanehara, Rieko; Yamaji, Taiki; Katagiri, Ryoko; Mutoh, Michihiro; Tsunematsu, Yuta; Sato, Michio; Watanabe, Kenji; Hosomi, Koji; Kakugawa, Yasuo; Ikematsu, Hiroaki; Hotta, Kinichi; et al.
Abstract: Escherichia coli containing polyketide synthase in the gut microbiota ( pks + E coli ) produce a polyketide‐peptide genotoxin, colibactin, and are suspected to play a role in the development of colorectal neoplasia. To clarify the role of pks + E coli in the early stage of tumorigenesis, we investigated whether the pks status of E coli was associated with the prevalence of colorectal neoplasia. This cross‐sectional analysis of data from a prospective cohort in Izu Oshima, Japan included asymptomatic residents aged 40‐79 years who underwent screening colonoscopy and provided a stool sample. We identified 543 participants with colorectal neoplasia (22 colorectal cancer and 521 adenoma) as cases and 425 participants with normal colon as controls. The pks s tatus of E coli was assayed using stool DNA and specific primers that detected pks + E coli . The proportion of pks + E coli was 32.6% among cases and 30.8% among controls. Compared with those with pks − E coli, the odds ratio (OR) (95% confidence interval) for participants with pks + E coli was 1.04 (0.77‐1.41) after adjusting for potential confounders. No statistically significant associations were observed regardless of tumor site or number of colorectal adenoma lesions. However, stratified analyses revealed increased ORs among participants who consumed cereals over the median intake or vegetables under the median intake. Overall, we found no statistically significant association between pks + E coli and the prevalence of colorectal adenoma lesions among this Japanese cohort. However, positive associations were suggested under certain intake levels of cereals or vegetables. Abstract : Overall, we found no statistically significant association between Escherichia coli containing polyketide synthase in the gut microbiota and the prevalence of colorectal adenoma lesions, based on a cross‐sectional analysis among this Japanese cohort aged 40‐79 years who underwent screening colonoscopy. On stratified analysis, however, positive associations were seen in participants with cereal intake above the median and in those with vegetable intake below the median.